A double dealing tale of p63: an oncogene or a tumor suppressor - Chen, Yonglong; Peng, Yougong; Fan, Shijie; Li, Yimin; Xiao, Zhi-Xiong; Li, Chenghua (Cellular and molecular life sciences : CMLS, 2018)
As a member of tumor suppressor p53 family, p63, a gene encoding versatile protein variant, has been documented to correlate with cancer formation and progression, though it is rarely mutated in cancer patients. However, it has long been controversial on whether p63 is an oncogene or a tumor suppressor. Here, we comprehensively reviewed reports on roles of p63 in development, tumorigenesis and tumor progression. According to data from molecular cell biology, genetic models and clinic research, we conclude that p63 may act as either an oncogene or a tumor suppressor gene in different scenarios: TA isoforms of p63 gene are generally tumor-suppressive through repressing cell proliferation, survival and metastasis; ΔN isoforms, however, may initiate tumorigenesis via promoting cell proliferation and survival, but inhibit tumor metastasis and progression; effects of p63 on tumor formation and progression depend on the context of the whole p53 family, and either amplification or loss of p63 gene locus can break the balance to cause tumorigenesis.